Upper extremity analyses of standing throw with three weights of shot put - Peng, H.; Huang, C.; Peng, H. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of this study was to analyse kinematic valuables of the throwing extremity with three weights of shot put. Three-dimensional method was used to analyze the upper extremity of shot putters performing standing throws. Nonparametric statistical test of Friedman two-way analysis of variance by ranks was conducted for the valuables (p=.05). There were significant differences between 8 lb. and 16 lb. shot put in the measure distance, release velocity and maximal angular momentum of the forearm. The proximalto- distal sequencing was found in terms of segment angular momentum.